Pemanfaatan ICT Dan Fintech: Pentingkah Bagi Pelaku UMKM - Astuti, Maesaroh Risqi Dwi; Hanafi, Rustam; Sutapa, Sutapa (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2024)
In line with the development of information technology, Micro, Small, and Medium Enterprises (MSMEs) must adapt and adopt technology to increase efficiency and expand market reach to improve MSMEs' performance. Therefore, this study aims to examine the role of Information Communication Technology (ICT) and financial technology (fintech) on the performance of MSMEs. Data was collected through questionnaires to MSMEs respondents in Pati Regency. This study uses multiple linear regression to test the proposed hypothesis. The results of this study show that Information Communication Technology (ICT) and Financial technology (fintech) have a significant positive effect on the performance of MSMEs.